2017
DOI: 10.1111/jdi.12605
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of premixed insulin analogs in Asian patients with type 2 diabetes: A systematic review

Abstract: Aims/IntroductionThe primary aim of this systematic review was to provide an overview of the efficacy and safety of premixed insulin analogs in Asians, specifically East Asians, with type 2 diabetes.Material and MethodsThe MEDLINE, Embase, Cochrane Library and ClinicalTrials.gov databases were searched from 1 January 1995 to 26 November 2015. Randomized controlled trials involving East Asians with type 2 diabetes treated with any premixed insulin analog were included. Major comparator treatments were basal ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 34 publications
(192 reference statements)
0
12
0
Order By: Relevance
“…Consistent with our results, the DURABLE study ( 20 , 21 ) showed that a premixed insulin analog had a slightly higher proportion of patients attaining the target HbA1c than basal insulin. However, a systematic review recently reported that the change of HbA1c was not significantly different between the premixed insulin analog and basal groups ( 14 ). Several reasons might be account for the better efficacy of premixed insulin in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with our results, the DURABLE study ( 20 , 21 ) showed that a premixed insulin analog had a slightly higher proportion of patients attaining the target HbA1c than basal insulin. However, a systematic review recently reported that the change of HbA1c was not significantly different between the premixed insulin analog and basal groups ( 14 ). Several reasons might be account for the better efficacy of premixed insulin in our study.…”
Section: Discussionmentioning
confidence: 99%
“…In China, Ji and colleagues showed that after failure of oral hypoglycemic medications, initiating treatment with premixed insulin was able to achieve glycemic control in 70% of T2DM patients ( 13 ). A systematic review study of randomized controlled trials showed that premixed insulin can be a simple and effective means of T2DM treatment in East Asians, and its safety is generally similar to that of basal or basal-bolus insulin ( 14 ). In the hospital setting, premixed insulin was reported to be effective in improving hyperglycemia and controlling HbA1c in T2DM inpatients, and the effect was also similar to inpatients receiving basal insulin ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…Use of premixed formulations for initiation of insulin therapy is particularly common in East Asian patients with T2DM as a result of the higher prevalence of postprandial hyperglycemia vs Caucasians with T2DM [ 61 ]. A number of RCTs compared the efficacy and safety of IGlar (with/without prandial insulin) with that of premixed human and analog insulins for initiation [ 62 – 67 ] or intensification [ 68 70 ] of insulin therapy in East Asians with T2DM (Table 3 ).…”
Section: Insulin Glargine Vs Other Injectable Treatments In Patients mentioning
confidence: 99%
“…Premixed insulin analogs have efficacy and safety outcomes similar to those of basal or basal-bolus insulin [ 24 , 25 ]. In a review comparing premixed and basal plus regimens, Downie et al reported similar efficacy and safety with both regimens for both insulin initiation in insulin-naïve patients and intensification in patients who have failed on basal insulin [ 26 ].…”
Section: Premixed Insulin: Initiation and Intensificationmentioning
confidence: 99%